An Integrative Model of Digital Entrepreneurship for Enhancing MSME Sustainability in Bogor Regency - Sandy Wibisono; Sulistiono Sulistiono; Sujana Sujana; Theresia Celine Nata Atmaja (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study develops and empirically tests an integrative model of how digital literacy, digital entrepreneurship, and digital innovation influence the sustainability of micro, small, and medium enterprises (MSMEs) in Bogor Regency, Indonesia. Using a quantitative approach and a cross-sectional survey of 180 MSME owners, the research applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the causal relationships among the key constructs. The findings reveal that digital literacy has a strong and significant effect on digital entrepreneurship (β = 0.694), highlighting the importance of foundational digital skills for cultivating entrepreneurial behaviors in digital contexts. Digital entrepreneurship is also found to significantly influence digital innovation (β = 0.726), indicating that proactive and opportunity-oriented digital entrepreneurs are more likely to adopt and implement innovative digital practices. Furthermore, digital innovation plays a substantial role in enhancing MSME sustainability (β = 0.542), while digital entrepreneurship also contributes directly to sustainability (β = 0.384). The integrative model accounts for 64.5% of the variance in sustainability, demonstrating strong explanatory power. These results underscore that sustainable MSME development in the digital era requires not only technological access but also strengthened digital literacy, entrepreneurial capability, and innovative behavior. The study provides theoretical insights into digital capability frameworks and practical guidance for designing policies and programs that support MSME digital transformation in semi-urban regions such as Bogor Regency. KEYWORDS: Digital literacy; Digital entrepreneurship; Digital innovation; MSME sustainability; PLS-SEM; Bogor Regency; Digital transformation; Small business development.